(untitled) (Journal of Sciences & Technology, 2021)
The authors present the numerical study of the phenomenon of the natural, laminar and permanent convection in an elliptic annular cavity delimited by two diametrical plans and is tilted at an angle  with respect to the horizontal plane. The enclosure considered is of practical interest (Storage, Isolation). It is filled by a Newtonian and incompressible fluid, in laminar and permanent mode. The Prandtl number is fixed at 0.7 (air) but the Grashof number varies. They determine the distributions of the temperature and the stream-function in the fluid and indicate the influence on the flow of the Grashof number and the system tilt.